Mothers of invention : women of the slaveholding South in the American Civil War - Faust, Drew Gilpin (Fred W. Morrison series in Southern studies., 1996)
This study offers an insight into the lives of the women who belonged to the slaveholding families of the Confederacy during the American Civil War. It describes how they had to direct farms and plantations, provide for families and supervise increasingly restive slaves.